Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.ejpain.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐dose intranasal (S)‐ketamine in patients with neuropathic pain

Abstract: Intranasal administration of low dose (S)-ketamine rapidly induces adequate plasma concentrations of (S)-ketamine and subsequently of its metabolite (S)-norketamine. The time course of analgesia correlated with plasma concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 37 publications
0
52
1
1
Order By: Relevance
“…Intranasal delivery of pain medication is an attractive, convenient, efficient, cheap and rapid form of pain control in the ED where time, manpower, space and proper monitoring to all patients with pain are not feasible, especially in the setting where IV initiation or opioid administration exists. Researchers [11,12] have reported that the nose-brain pathway leads to a rapid delivery of some nasal medications across the olfactory mucosa to the cerebral spinal fluid and the brain, bypassing the first pass metabolism and the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intranasal delivery of pain medication is an attractive, convenient, efficient, cheap and rapid form of pain control in the ED where time, manpower, space and proper monitoring to all patients with pain are not feasible, especially in the setting where IV initiation or opioid administration exists. Researchers [11,12] have reported that the nose-brain pathway leads to a rapid delivery of some nasal medications across the olfactory mucosa to the cerebral spinal fluid and the brain, bypassing the first pass metabolism and the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that IN ketamine is an effective safe and well tolerated method of analgesia in burn dressing [13] and pediatric laceration repair, [14] in control of post-operative pain [2] and neuropathic pain, [12] and in prehospital setting [15] and the ED. [5][6][7] In 1996 Kulbe et al [13] published a case report confi rming that intranasal ketamine spray can be effective for acute pain control during burn dressing changes, suggesting this was an area that deserved further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are at least 9 randomized, double-blind trials demonstrating the efficacy of ketamine in NP [66][67][68][69][70][71][72][73][74][75]. In patients with post-nerve injury NP, ketamine administered IV has shown significant reduction in pain and allodynia as compared to placebo [66-70, 73, 74] as well as compared to morphine [73].…”
Section: Literature On Ketamine Use In Peripheral Neuropathic Painmentioning
confidence: 99%
“…Intranasal use of the more potent enatiomer (S) ketamine at doses of 0.2 and 0.4 mg/kg was studied in 16 patients with NP and showed a significant reduction in NP that was dose-dependent, lasting 2-3 h with maximum pain reduction of 30-40 % at 50 min after application [72]. The two randomized, double-blind, placebo-controlled studies on topical administration of ketamine did not show efficacy in the treatment of peripheral NP with no effect from ketamine 1 % topical cream applied three times daily for 3 weeks in 92 patients with peripheral NP [76] or when ketamine 5 % topical cream was applied for 1 month in 17 patients with diabetic peripheral neuropathy [75].…”
Section: Literature On Ketamine Use In Peripheral Neuropathic Painmentioning
confidence: 99%